2007
DOI: 10.1590/s0103-05822007000200010
|View full text |Cite
|
Sign up to set email alerts
|

Sala de emergência em pediatria: casuística de um hospital universitário

Abstract: OBJETIVO: Descrever a casuística de pacientes pediátricos atendidos em sala de emergência pediátrica de um hospital universitário. MÉTODOS: Estudo retrospectivo descritivo de 1º de janeiro até 31 de dezembro de 2004, com crianças de zero a 14 anos, avaliadas quanto a dados epidemiológicos, hipótese diagnóstica, intubação orotraqueal, óbito, destino e duração da internação. Os pacientes foram divididos em quatro grupos: Não Óbitos; Óbitos <24 horas, Óbitos >24 horas e transferidos para outros hospitais. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
3
3
2
1
Order By: Relevance
“…Out of the total number of patients in this study, 19.1% needed orotracheal intubation and invasive ventilator support, similarly to what has been described by Riccetto et al 9 , who observed that 24.6% of the patients analyzed in their study needed intubation in the pediatric emergency room. This significant need for invasive procedures (orotracheal intubation) reinforces the importance of adequate equipment and specialized professionals.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Out of the total number of patients in this study, 19.1% needed orotracheal intubation and invasive ventilator support, similarly to what has been described by Riccetto et al 9 , who observed that 24.6% of the patients analyzed in their study needed intubation in the pediatric emergency room. This significant need for invasive procedures (orotracheal intubation) reinforces the importance of adequate equipment and specialized professionals.…”
Section: Resultssupporting
confidence: 88%
“…Patients admitted to SERUPE were mostly from the male gender (53.2%), which is the same percentage as the one found in a study conducted by Caldeira et al 8 . Riccetto et al 9 identified that infants and preschoolers are more prone to severe conditions that may lead to hospital admission, such as in this study, in which 59.2% of the participants were younger than 5 years old, and, therefore, were in the same age group as the one in the previously mentioned study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Another study described a series of children treated in the emergency room and found that 65% of patients were previously healthy and that the reason for the consultation was for treatment in medical clinic (1) .…”
Section: Discussionmentioning
confidence: 99%
“…The unnecessary search for hospital emergency, both in developed and developing countries such as Brazil, concerns poverty and the low level of maternal education in addition to the level of misinformation about the complexity of the treatment to be sought by parents or guardians face to the child's illness (1,2) .…”
Section: Introductionmentioning
confidence: 99%